Mission Impossible? Challenging Police Credibility in Suppression Motions - Liu, Siyu (Criminal justice policy review, 2022)
Suppression motions are the means by which defendants challenge the constitutionality of stops, searches, and seizures, and move the court to exclude illegally recovered evidence. However, defendants face insurmountable obstacles in challenging police credibility in these motions. Using 31 motions with factual disputes from a northeastern state, we dissect the types of defense challenges related to stops, searches, seizures, and arrests, as well as the prevalence and types of corroborating evidence presented by the defense. We find that most defense challenges to police credibility are not corroborated, and evidence of prior police misconduct is not presented. Furthermore, judges typically rule in favor of the police when adjudicating uncorroborated factual disputes between police officers and defendants. As a result, suppression motions generally fail to serve as an accountability structure for police conduct and rarely provide defendants with a viable remedy to address rights violations.